Assessing The Validity Of The Halal Consumption Congruence (Hacc) Model Towards Consumer’s Purchase Intention Of Malaysia’s Halal Food Products - Said, Mahiah; Hassan, Faridah; Hasim, Muhammad Asyraf; Mohamad Yazid, Faizun (J Fatwa, 2025)
Halal industry is one of the fastest growing industries in the world and Malaysia contributed about US$113.2 billion. To protect Malaysia’s reputation as the top halal food producers, monitoring the Muslim consumers’ attitude and preference towards the Malaysia’s halal products is imperative. This study provides some insights since there are limited study on Malaysian halal food product specifically. 402 respondents from of Middle Eastern origin participated by completing self-administered questionnaire. This study integrated Theory of Planned Behaviour and Congruity Theory. Country-of-origin and religiosity commitment are selected since both are common constructs for halal behavioural study. The results showed that consumer self-congruence, religiosity commitment and perceived behavioural control have significant relationship with purchase intention. The opposite outcomes are country-of-origin and subjective norms. Attitude has a mediating effect towards the relationships of country-oforigin, consumer self-congruence, and religiosity commitment with purchase intention. In the interim, customer trust shows a significant moderating role towards purchase intention. Measuring religiosity is rather tricky and difficult because to admit non-conformance to the Islamic rites and requirements especially the “wajib” (must do) rites are something to be ashamed of. Furthermore, the respondents were Muslims from only six Middle Eastern countries, the findings could not be generalized. Future research should delve into the nonMuslims and other constructs that could enhance the research model. Conclusively, this study produces a novel research approach through the development of Halal Consumption Congruence (HaCC) Model that provide vital guidelines for Malaysia’s halal food producers in enticing the Muslim consumers’ purchase behaviour.